2006
DOI: 10.1021/jp057229r
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Dynamics of Fragmentation of Protonated Leucine Enkephalin from Time- and Energy-Resolved Surface-Induced Dissociation Studies

Abstract: Dissociation of singly protonated leucine enkephalin (YGGFL) was studied using surface-induced dissociation (SID) in a Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS) specially configured for studying ion activation by collisions with surfaces. The energetics and dynamics of seven primary dissociation channels were deduced from modeling the time- and energy-resolved fragmentation efficiency curves for different fragment ions using an RRKM-based approach developed in our laboratory. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(127 citation statements)
references
References 59 publications
(153 reference statements)
6
120
1
Order By: Relevance
“…Internal fragments GF-28, GF, GGF, and FYG are observed as well. Laskin 24 found a strong time dependence of a 4 -NH 3 and FYG and concludes that these fragments are associated with the cyclic rearrangements previously mentioned. This cyclic a 4 rearrangement has already been invoked earlier by Vachet and co-workers.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Internal fragments GF-28, GF, GGF, and FYG are observed as well. Laskin 24 found a strong time dependence of a 4 -NH 3 and FYG and concludes that these fragments are associated with the cyclic rearrangements previously mentioned. This cyclic a 4 rearrangement has already been invoked earlier by Vachet and co-workers.…”
Section: Discussionmentioning
confidence: 62%
“…When we assume that the excitation of one of the peptide bonds is followed by IVR, we can directly compare our results to the SID studies by Laskin. 24 For 50 eV protonated leu-enk collisions with a self-assembled alkane thiolate monolayer, a maximum of about 17% of the collision energy is transferred into the peptide 38 implying about 8.5 eV of internal energy-about the same as deposited by 8 or 9 eV photoexciation here. The SID spectrum, qualitatively similar to our photoexcitation data [see Fig.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Time-resolved SID studies have been conducted in an FT-ICR by varying the trapping time following peptide ion-surface collision [103][104][105][106]. These studies revealed the time dependence of peptide fragmentation when the observation time frame ranged from 1 ms to several seconds.…”
Section: Kinetics Of Peptide Fragmentationmentioning
confidence: 99%